COMPARATIVE ANALYSIS OF THE E-GOVERNMENT DEVELOPMENT INDEX: A CASE STUDY OF SINGAPORE AND AFGHANISTAN - Ramadhan, Sukma Aditya; Purnomo, Eko Priyo (Universitas Padjadjaran, 2024)
This study analyzes the differences in the development of e-government in Singapore and Afghanistan using the E-Government Development Index (EGDI) indicators which include the Online Services Index (OSI), Human Capital Index (HCI), and Telecommunication Infrastructure Index (TII). The findings show that Singapore's success in e-government is underpinned by strategic investments in ICT infrastructure, the adoption of innovative policies such as the